Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/wfs2.1403
|View full text |Cite
|
Sign up to set email alerts
|

The forensic exploitation of fingermark chemistry: A review

Abstract: The substances deposited from the fingertip onto a surface during contact between them represent a highly complex range of chemicals that can be exploited in a variety of ways in a forensic investigation. An overview is given of the multitude of chemicals that have been detected in fingermarks, including those occurring in endogenous sweat, metabolites of ingested substances, and exogenous substances picked up on the fingertip. Changes in chemistry that may occur between deposition of the fingermark and its su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 233 publications
2
26
0
Order By: Relevance
“…In a few cases, it has been possible to show that MALDI MSI provided additional ridge detail in partially developed or empty marks [19]. In line with previous reports on constituents availability after the application of a single FET [1], MALDI is able to detect and image constituents or classes of compounds even after being targeted by a prior FET [19,22] and even in specimens over 30 years old [9]. Additionally, four examples have been published in which MALDI MSI was shown to be compatible with fingermark sequential processing.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a few cases, it has been possible to show that MALDI MSI provided additional ridge detail in partially developed or empty marks [19]. In line with previous reports on constituents availability after the application of a single FET [1], MALDI is able to detect and image constituents or classes of compounds even after being targeted by a prior FET [19,22] and even in specimens over 30 years old [9]. Additionally, four examples have been published in which MALDI MSI was shown to be compatible with fingermark sequential processing.…”
Section: Introductionsupporting
confidence: 86%
“…Latent fingermarks are routinely visualised by subjecting them to one or more crime scene investigation (CSI)/crime lab processes to maximise recovery of ridge flow and minutiae permitting an identification. Sequential processing is possible as a single chemical development reagent can still leave a considerable proportion of fingermark constituents that can be targeted by an additional enhancement technique [1]. When these enhancement techniques are used in a sequence, an optimum order of application is recommended , starting from the least destructive when possible, to maximise the biometric detail that can emerge from the different fingermark constituents.…”
Section: Introductionmentioning
confidence: 99%
“…or even by handshakes between a smoker and a non-smoker [ 8 , 9 ]. The last few years have shown an increasing application of various chemical imaging techniques in forensic science [ 10 , 11 , 12 , 13 , 14 , 15 ], especially in detecting exogenous materials present on fingermarks, such as particles of nicotine [ 9 ], gunshot residues [ 16 , 17 , 18 , 19 ], illicit drugs [ 6 , 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 ], caffeine [ 24 , 25 ], blood [ 26 ], explosive RDX residues [ 20 , 27 ], or in determining the sequencing of fingerprint and ink signals on documents [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fingermark residue is made primarily of a mixture of secretions from the eccrine and sebaceous glands, and is likely to be contaminated with constituents picked up through contact during daily activity. [4][5][6] Once deposited, this residue is not static with a potential to move across a surface, and undergo chemical and physical changes. Sebaceous material is an oily mixture of lipids, which are known to degrade over time, studies have attempted to correlate this rate of degradation to time since fingermark deposition.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 Keisar et al calculated the mass of a fingermark to be between 2 -9 µg, based on the weight of a smaller subsection of the mark, whilst Bleay et al reported a mass range of 0.33 -29 µg. 6,18 Several studies have explored fingermark degradation, by visually comparing how fingermark development methods are affected by evaporation and time since deposition. 14,17,20,21 An alternative approach has been to explore the chemical alteration within fingermark residue, by directly measuring the chemical constituents present at different time points since deposition, using techniques such as gas chromatography (GC) and liquid chromatography -mass spectroscopy (LC-MS).…”
Section: Introductionmentioning
confidence: 99%